Performance of ginger and turmeric genotypes in Raigarh District of Chhattisgarh - Yadav, R K (Journal of Spices and Aromatic Crops, 2002)
Eleven turmeric and six ginger genotypes were evaluated at Regional Agricultural Research Station, Boirdadar, Raigarh, Chhattisgarh. All the entries were found better than the local genotypes used as checks. Varada gave the highest rhizome yield (175.3 q ha-1) followed by V3S1 8 (174.0 q ha-1) in ginger and turmeric PTS-43 gave the maximum fresh rhizome yield (255.9 q ha-1) which was closely followed by JTS-2 (251.2 q ha-1), Acc. 360 (246.9 q ha-1), Raj Sonia (234.9 q ha-1) and JTS-1 (231.6 q ha-1). These genotypes can be popularized for cultivation in Raigarh District of Chhattisgarh for increasing the production of ginger and turmeric.